1993
DOI: 10.1111/j.1532-5415.1993.tb06948.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Impairment and Quality of Life in a Community Elderly Population

Abstract: The quality of life of community-dwelling elderly people is significantly linked to sensory impairment, which can be detected through simple physical examination. Mood level and social relationships are particularly affected by visual impairment, whereas self-sufficiency in daily living is more strongly related to hearing impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
270
7
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(310 citation statements)
references
References 53 publications
18
270
7
2
Order By: Relevance
“…Vision is central to the functioning of the individual and it is clear from numerous studies over the past two decades that impaired vision exerts dramatic effects on function and on quality of life [8][9][10][11][12][13][14]. It has also been shown that interventions which improve visual function, such as cataract surgery, also improve HRQOL [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Vision is central to the functioning of the individual and it is clear from numerous studies over the past two decades that impaired vision exerts dramatic effects on function and on quality of life [8][9][10][11][12][13][14]. It has also been shown that interventions which improve visual function, such as cataract surgery, also improve HRQOL [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that older adults who are hearing impaired have greater functional disability when compared with their nonimpaired peers [10,12,15,18,[26][27][28]. However, this relationship does not appear to be as strong when compared with the relationship between visual impairment and ADL/IADL disability [25,[29][30].…”
Section: Hearing Impairmentmentioning
confidence: 99%
“…Research has found a strong relationship between visual impairment and functional disability among community-based older adults, even after controlling for demographic and comorbid health conditions [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. When compared with other physical impairments, visual impairment also has a more severe effect on everyday functioning and is as limiting as terminal cardiac disease in older adults [23].…”
Section: Visual Impairmentmentioning
confidence: 99%
“…20,21 Furthermore, visual impairment impacts on a wide range of objective and subjective measures of functional status, including those measures which are not actually vision dependant, such as psychological well being. 16,18,[22][23][24][25] One of the principle aims of the current study was to develop a simple bedside screening test that could be incorporated into the rehabilitation package offered to patients who fall sustaining a fractured neck of femur. While not without its limitations, high-contrast Snellen visual acuity is still deemed to be a useful indicator of the ability of an older patient to perform a range of visiondependant daily living tasks.…”
Section: Eyementioning
confidence: 99%